2019
DOI: 10.1097/bot.0000000000001437
|View full text |Cite
|
Sign up to set email alerts
|

Early Immunologic Response in Multiply Injured Patients With Orthopaedic Injuries Is Associated With Organ Dysfunction

Abstract: Objectives: To quantify the acute immunologic biomarker response in multiply injured patients with axial and lower extremity fractures and to explore associations with adverse short-term outcomes including organ dysfunction and nosocomial infection (NI). Design: Prospective cohort study. Setting: Level 1 academic trauma center. Patients: Consecutive multiply inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 40 publications
7
26
0
Order By: Relevance
“…We have also demonstrated previously that two of these chemokines (MCP-1 and IP-10) are biomarkers of adverse outcomes in trauma [48, 51]. Circulating levels of the cytokine IL-6 were statistically significantly different between groups by AUC analysis, again in line with a previous study in a separate cohort of extremity fracture patients [57]. The role of IL-6 in this setting may be quite central, since recent studies have reported improved fracture healing in an animal model of bone fracture following administration of neutralizing antibodies directed against the IL-6 receptor [58].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We have also demonstrated previously that two of these chemokines (MCP-1 and IP-10) are biomarkers of adverse outcomes in trauma [48, 51]. Circulating levels of the cytokine IL-6 were statistically significantly different between groups by AUC analysis, again in line with a previous study in a separate cohort of extremity fracture patients [57]. The role of IL-6 in this setting may be quite central, since recent studies have reported improved fracture healing in an animal model of bone fracture following administration of neutralizing antibodies directed against the IL-6 receptor [58].…”
Section: Discussionsupporting
confidence: 88%
“…This network phenotype was associated with significantly elevated levels of several chemokines and cytokines. These included the chemokines IL-8, MIG, IP-10, and MCP-1; we have reported elevations of these mediators in a separate study of extremity fracture patients [57]. We have also demonstrated previously that two of these chemokines (MCP-1 and IP-10) are biomarkers of adverse outcomes in trauma [48, 51].…”
Section: Discussionmentioning
confidence: 87%
“…Additional work is needed to validate the predictive power of these computational models, and reproducibility in experiments with human clinical samples remains to be determined. Of note, recent clinical studies have taken a similar approach by analyzing serum/ plasma from trauma patients and finding that levels of certain cytokines were associated with greater immune dysregulation and multiple organ dysfunction (54,55). In that same vein, the results from this study can motivate further investigation into systemic immune profiles as a potentially powerful tool for early prediction of trauma healing outcomes.…”
Section: Discussionmentioning
confidence: 72%
“…This was demonstrated by increased release of organ-specific transaminases as specific indicators of injury, as well as by enhanced activity loss and mortality 27,30,52 . Furthermore, IL-6 is enhanced in polytraumatized patients and predictive for the clinical outcome 53,54 . Thus, the data from the underlying study showing the highest systemic and local inflammatory changes with enhanced proinflammatory cytokines and infiltrates with inflammatory cells concurrent with organ damage in the hemorrhagic shock model, as well as in all models of multiple trauma including shock, are supporting the clinical and previous experimental reports.…”
Section: Discussionmentioning
confidence: 99%